Feasibility of Vermicomposting of Spent Coffee Grounds and Silverskin from Coffee Industries: A Laboratory Study - M.A. González-Moreno; B. García Gracianteparaluceta; S. Marcelino Sádaba; J. Zaratiegui Urdin; E. Robles Domínguez; M.A. Pérez Ezcurdia; A. Seco Meneses (Agronomy, 2020)
In the coffee industry, several by-products are generated during the production and consumption of coffee and represent an important waste from an environmental viewpoint. For improving the knowledge about this issue, a laboratory vermicomposting study of coffee silverskin (CS) and spent coffee grounds (SCG) spiked with mature horse manure (HM) in different proportions and using earthworm Eisenia andrei was carried out. The 60-day study focused on biological parameters such as total biomass gain, growth rate, cocoon production, and mortality. This study also investigated whether the vermicompost obtained could be useful and lacked toxicity through a seed germination test using hybrid wheat seeds. Results showed a disparity depending on the type of residue and the mixture used. Best options were those treatments with a medium–low amount of residue; 25% for SCG and 25% or 50% for CS. In addition, lack of toxicity was confirmed in all treatments. In conclusion, it is possible to carry out a vermicomposting of SCG and CS with some specific features.